How does parent/self‐reporting of common respiratory conditions compare with medical records among Aboriginal and Torres Strait Islander (Indigenous) children and young adults?. (4th May 2019) - Blake, Tamara L; Chang, Anne B; Chatfield, Mark D; Marchant, Julie M; Petsky, Helen L; McElrea, Margaret S
Abstract : Aim: Self‐reporting and/or data from medical records are frequently used in studies to ascertain health history. Data on the discrepancies between these information sources is lacking for Indigenous Australians. This study reports such data for selected respiratory and atopic conditions common among Indigenous Australians. Methods: Data were extracted from the Indigenous respiratory reference value study, a multicentre cross‐sectional study of Indigenous children and young adults (3–25 years) between June 2015 and November 2017. Only those living in rural/remote regions were included. Self‐reported history was collected from parents (if participants <18 years) or participants. Medical records were manually reviewed. Participants with incomplete data (missing self‐reported and/or medical record information) were excluded. Agreement between sources was examined using Cohen's kappa. Results: Of 1097 participants, 889 (97.1% <18 years) had sufficient self‐reported and medical record histories for comparison. Asthma was self‐reported by 15.7% of participants and was reported in medical records for 10.3% ( κ = 0.53, 95% confidence interval (CI) 0.45–0.61). For bronchiectasis, the reported rates were 1.5 and 0.7% ( κ = 0.52, 95% CI 0.25–0.80), pneumonia 1.1 and 5.8% ( κ = 0.15, 95% CI 0.02–0.27), allergic rhinitis 6.6 and 0.6% ( κ = 0.05, 95% CI −0.03, 0.13) and eczema 5.8 and 6.2% ( κ = 0.30, 95% CI 0.18–0.42). Conclusions: Within our cohort, agreement was moderate for asthma and bronchiectasis, fair for eczema and poor for pneumonia and allergic rhinitis. These results highlight the challenges associated with how best to obtain an accurate health history within Australian Indigenous rural/remote communities. Generalisability of findings and contributions of poor health knowledge and/or poor medical record documentation need further exploration.